Orofacial Praxis Abilities in Children with Speech Disorders - Bertagnolli, Ana Paula Coitino; Gubiani, Marileda Barichello; Ceron, Marizete; Keske-Soares, Márcia (International Archives of Otorhinolaryngology, 2015)
Introduction Phonological development occurs in a gradual manner until the age of 7 years. The phonological system is constructed in a similar way for all children, despite presenting some variations in terms of age, paths taken, or repair strategies used.Objective To compare the orofacial praxis abilities of children with typical phonological development (DFT), children with phonetic-phonological impairment (DFoFe), and children with phonological impairment (DF), using two tests to assess the orofacial praxis abilities.Methods The sample consisted of 82 subjects between 4 and 8 years of age who attended public schools (from preschool to the second year of secondary school) in the city of Santa Maria, Brazil. Of these, 29 were diagnosed with DFT, 29 with DF, and 24 with DFoFe; much of this sample was male. Two tests of praxis abilities and assessment of the stomatognathic system were administered. Statistical analysis was performed using the chi-square test, with a significance level of 5%.Results Generally children with DFoFe underperformed in tests of praxis when compared with subjects with DF and DFT.Conclusion The results showed that children with DFoFe have more difficulty in orofacial praxis abilities than subjects in the other groups studied. This result could be expected, because subjects with DFoFe show changes in both phonetic and phonological levels of speech.
Keywords: speech; child; articulation disorder; stomatognathic system; speech disorders